The clinical impact of additional late PET/CT imaging with 68Ga-PSMA-11 (HBED-CC) in the diagnosis of prostate cancer - Afshar-Oromieh, Ali; Sattler, Lars Peter; Mier, Walter; Hadaschik, Boris; Debus, Jürgen; Haberkorn, Uwe (Journal of nuclear medicine, 2017)
Although PET/CT with 68Ga-PSMA-11 in the diagnosis of prostate cancer (PCa) is routinely performed at 1 h after injection, later scans may be beneficial because most lesions present with higher uptake and contrast. This evaluation aimed to investigate the clinical impact of additional late 68Ga-PSMA-11 PET/CT. Methods: Between 2011 and 2016, 112 patients with PCa who underwent early (at 1 h after injection) and late (at 3 h after injection) 68Ga-PSMA-11 PET/CT scans were retrospectively evaluated. The late scans were conducted to clarify unclear findings in early scans or to increase the probability of tumor detection in the case of negative early scans. All patients were asked to drink 1 L of water between early and late scans. In addition, 20 patients received 20 mg of furosemide before late scans. Tumor detection and radioactivity concentration within the urinary bladder were analyzed in both scans. The SUVmax and contrast of 149 tumor lesions were measured in 69 patients with pathologic findings. Results: Overall, 134 lesions characteristic for PCa in 57 patients clearly presented at 1 h after injection and 147 lesions in 68 patients at 3 h after injection. Forty-three patients showed no pathologic findings. Eight patients (7.1%) showed 1 unclear finding in early scans, which could be clarified as characteristic for PCa at 3 h after injection. Four patients (3.6%) presented with 1 lesion characteristic for PCa at 3 h after injection only. Twelve patients (10.7%) presented with 12 possible PCa lesions at 1 h after injection, which, however, could not be confirmed as PCa in late scans. Two patients presented with 1 lesion characteristic for PCa at 1 h after injection, which became invisible at 3 h after injection because of low contrast. At 3 h after injection, 62.4% of the lesions demonstrated a higher SUVmax and 65.1% a higher contrast than at 1 h after injection. Patients with furosemide presented with lower SUV and radioactivity concentration within the urinary bladder. Conclusion: 68Ga-PSMA-11 PET/CT at 3 h after injection showed most lesions characteristic for PCa with a higher uptake and contrast. In addition, the radioactivity signal within the urinary bladder was lower at 3 h after injection, especially when furosemide was applied. Consequently, scans at 3 h after injection detected more tumor lesions than at 1 h after injection.